The nexus between natural-hazard-related deaths and macroeconomic factors - Kose, Nezir; Unal, Emre; Keeley, Alexander Ryota; Managi, Shunsuke (Springer, 2026)
This study employs a suite of empirical methodologies, including panel data analysis, a vector autoregression model, and panel Granger causality tests, to examine the impact of deaths caused by natural hazards on key macroeconomic indicators across a sample of seven developed and 12 developing countries. Our analysis considers variables such as GDP, exports, imports, investments, exchange rates, and natural-hazard-related deaths, while also incorporating the effects of the COVID-19 pandemic, over the period from 1970 to 2022. The instrumental variable/two-stage estimated generalized least squares model reveals that natural-hazard-related deaths exert a significant and deleterious influence on both GDP and exports. In contrast, they exert a substantial and positive impact on investment activities. The results of variance decomposition analysis indicate that deaths accounted for a considerable fraction of the total explanatory variance in most selected nations in the long term. The panel Granger causality test provides diverse insights that contribute to a nuanced understanding of the consequences of natural hazards. Overall, natural-hazard-related deaths do not exhibit substantial disparities in terms of their implications between developed and developing countries. Geography and regional sensitivity to natural hazards may play key roles in explaining the occurrence of such consequences.
Keywords: Exchange rate; Macroeconomic factor; Natural hazards; Panel Granger test; VAR model; C5; F1; F3